Harnessing the Angiogenic Potential of Stem Cell-Derived Exosomes for Vascular Regeneration - F. Alcayaga-Miranda; M. Varas-Godoy; M. Khoury (Stem Cells International)
Mesenchymal stem cells (MSCs) are known to display important regenerative properties through the secretion of proangiogenic factors. Recent evidence pointed at the key role played by exosomes released from MSCs in this paracrine mechanism. Exosomes are key mediators of intercellular communication and contain a cargo that includes a modifiable content of microRNA (miRNA), mRNA, and proteins. Since the biogenesis of the MSCs-derived exosomes is regulated by the cross talk between MSCs and their niche, the content of the exosomes and consequently their biological function are dependent on the cell of origin and the physiologic or pathologic status of their microenvironment. Recent preclinical studies revealed that MSCs-derived exosomes have a critical implication in the angiogenic process since the use of exosomes-depleted conditioned medium impaired the MSCs angiogenesis response. In this review, we discuss the current knowledge related to the angiogenic potential of MSCs-exosomes and methods to enhance their biological activities for improved vascular regeneration. The current gain of insight in exosomes studies highlights the power of combining cell based therapies and their secreted products in therapeutic angiogenesis.